The feminist case against pornography: a review and re-evaluation - Cawston A. (Inquiry (United Kingdom), 2019)
Despite sustained feminist criticism, the production and consumption of pornography does not show signs of waning. Here, I offer a critical review of the existing feminist anti-pornography debate, arguing that it has largely failed to provide suitable grounds for a stable and comprehensive critique, instead often indirectly providing theoretical resources for pornography to reinvent itself. This is a product, in my view, of a misguided focus on the pornographic object. Feminist critics are better served, I argue, by redirecting their critical gaze towards the consumers of pornography, and, in particular, to the attitudes such consumption reflects. To that end, I introduce an alternative, attitudinal approach that enables criticism of pornography as a reflection of sexist attitudes, as well as for its role in concealing these attitudes.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; cours; discipline; philosophie; philosophie politique; pornographie; premier cycle; périodes historiques; rapports sociaux de sexe; ressource en ligne; santé; sciences humaines; sex1911; sexisme; sexualité; systèmes d'oppressions; thématiques; violences; éthique

Race, racisme, discriminations: anthologie de textes fondamentaux - Bessone, Magali; Sabbagh, Daniel (Avocat du diable, 2015)
« La race n'est-elle qu'une chimère - une fiction collective aux effets pernicieux - ou est-elle un concept nécessaire à l'analyse et à l'éradication éventuelle du racisme et de ses conséquences? Cette catégorie ambiguë relève-t-elle de la biologie ou bien renvoie-t-elle à une réalité de nature socio-politique? Le racisme est-il d'abord un attribut des individus ou des institutions - un état mental fait de croyances et d'affects ou un système social? Toute discrimination raciale est-elle inévitablement raciste? Est-elle immorale et injuste même dans les cas où elle ne serait pas entièrement irrationnelle? Enfin, la discrimination positive est-elle justifiable? Telles sont quelques-unes des questions abordées dans ce recueil, qui propose une introduction au champ d'investigation que la race, le racisme et les discriminations constituent pour la philosophie - ici envisagée dans son articulation avec les sciences sociales. Il réunit dix textes majeurs, presque tous inédits en français. »
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; antiracisme; approches et analyses; cours; discipline; discriminations; europe; occident; phi4336; philosophie; premier cycle; privilèges; périodes historiques; racisme; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques; violences

Démédicaliser les corps, politiser les identités : convergences des luttes féministes et intersexes - Kraus, Cynthia; Perrin, Céline; Rey, Séverine; Gosselin, Lucie; Guillot, Vincent (Nouvelles Questions Féministes, 2008)
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; approches et analyses; belgique; capacitisme; corps; cours; discipline; discours dominant; europe; france; féminisme interdisciplinaire; féminisme matérialiste; hétérosexisme; identités LGBTQIA2+; intersexuation; inégalités; luxembourg; marginalisation; militance; médecine; philosophie; premier cycle; psychiatrie; périodes historiques; queer; régions géographiques; santé; sciences; sciences humaines; soc2014; soc2051; sociologie; systèmes d'oppressions; thématiques; transféminisme; violences; violences médicales

The flowers in your dustbin: Girls in the North American punk subcultures of the 1990s - Leblanc, Lauraine (Université Emory, 1997)
Girls in male-dominated youth subcultures confront ideologies of gender which remain largely invisible and often tacitly accepted in many women's everyday lives. Punk girls choose to construct their femininity within a highly male-dominated, "masculinist," context; girls are present in such youth subcultures, but the masculine definition of their norms problematizes their participation. Thus, punk girls struggle to accommodate female gender norms within subcultural identities which are deliberately coded as "masculine." Although young women in America encounter the norms of the female gender role on a daily basis, punk girls' negotiations between the norms of femininity and those of punk open these prescriptions to critical examination which they might not otherwise be accorded. In this dissertation, I explore accounts of punk girls' engagements with both mainstream and subcultural gender norms. In constructing this account of girls' lived experiences in the punk subculture, I rely primarily upon the phenomenology, or experiential narrative, of punk girls' everyday lives. I elicited these accounts within the context of conducting participant observation in the punk scenes of four North American cities (Atlanta, Montreal, New Orleans, and San Francisco) from 1993 to 1995, conducting ethnographic interviews with forty punk girls. In the following, I explore various facets of punk girls' engagements with gender norms, including punk girls' narratives of engagement with the subculture; the construction of punk as a discourse of masculinity; punk girls' stylistic, behavioral, and discursive reconstructions of femininity; punk girls' experiences of public harassment and sexual harassment, and their strategic responses to these. I argue that these girls use the punk subculture in order to carry out resistances to varied forms of gender oppression, thereby developing stronger self-concepts in the face of adversity.
Keywords: 1900-1999; 1990-1999; amériques; approches et analyses; atlanta; discipline; ethnographie; genre; harcèlement sexuel; masculinisme; montréal; mémoires/thèses; nouvelle-orléans; patriarcat; philosophie; périodes historiques; régions géographiques; résistance; san francisco; sciences humaines; systèmes d'oppressions; thématiques; violences